PEMANFAATAN TEKNOLOGI THERMAL ENERGY STORAGE NON-MEKANIK SEBAGAI PENGERING BAHAN PANGAN SINGKONG - Rizki Muliawan (Jurnal Teknologi Terapan, 2021)
A drying machine is a machine that is used to dry some food or product. The process of heating can be used to preserve some products because drying reduces moisture content in the product and bacterial can’t live without water. Solar pond system will use for the machine which caught and trap the heat from the sun. The fluid in a pond of solar pond system is saltwater and the salinity will be varied. The variation of saltwater will be 3.5%, 5%, and 7%. In the solar pond system, some coils will circulate the water towards the cabin. The coil is made of copper pipe which has a length of 20.5 meters. This coil serves as a heat exchanger charged with the heat exchange process in the solar pond system. The water in this coil is circulated by a water pump. Water is circulated to the heat exchanger which is just below the cabin. The product used is 500 grams of cassava. Cassava is dried with the skin peeled and sliced about 2 mm thick. From the experiments that have been done obtained the best saltwater concentration is 7% with a tub temperature lower by 40 °C, the cabin temperature reaches 34.1 °C, and the water reduced of product weight by 210 grams. The COPactual heating average obtained by this machine is 1,15 and the COPcarnot heating average obtained by this machine is 29,80. The efficiency average that obtained by this machine is 3,77%.